Wounding-induced stomatal closure requires jasmonate-mediated activation of GORK K+ channels by a Ca2+ sensor-kinase CBL1-CIPK5 complex - Förster, Sabrina; Waadt, Rainer (Developmental cell, 2019)
Summary - Guard cells integrate various hormone signals and environmental cues to balance plant gas exchange and transpiration. The wounding-associated hormone jasmonic acid (JA) and the drought hormone abscisic acid (ABA) both trigger stomatal closure. In contrast to ABA however, the molecular mechanisms of JA-induced stomatal closure have remained largely elusive. Here, we identify a fast signaling pathway for JA targeting the K+ efflux channel GORK. Wounding triggers both local and systemic stomatal closure by activation of the JA signaling cascade followed by GORK phosphorylation and activation through CBL1-CIPK5 Ca2+ sensor-kinase complexes. GORK activation strictly depends on plasma membrane targeting and Ca2+ binding of CBL1-CIPK5 complexes. Accordingly, in gork, cbl1, and cipk5 mutants, JA-induced stomatal closure is specifically abolished. The ABA-coreceptor ABI2 counteracts CBL1-CIPK5-dependent GORK activation. Hence, JA-induced Ca2+ signaling in response to biotic stress converges with the ABA-mediated drought stress pathway to facilitate GORK-mediated stomatal closure upon wounding.
Im Titel sind "+" und "2+" hochgestellt
Available online 6 December 2018
Gesehen am 31.05.2019